1995
DOI: 10.1136/hrt.73.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ethnic origin on the pattern of congenital heart defects in the first year of life.

Abstract: Objective-To assess the prevalence and patterns of congenital heart defects in infants requiring hospital admission in a defined population and to determine the differences in ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 15 publications
2
23
0
1
Order By: Relevance
“…6 A study done at Aga Khan University hospital by Hassan showed prevalence rate of CHD up to 4/1000 live births in Karachi. 7 Same as that reported in India.…”
Section: -5mentioning
confidence: 99%
“…6 A study done at Aga Khan University hospital by Hassan showed prevalence rate of CHD up to 4/1000 live births in Karachi. 7 Same as that reported in India.…”
Section: -5mentioning
confidence: 99%
“…11 Correa-Villasenor and colleagues reported an excess of white infants among cases with AS, PA, COA and D-TGA and a deficit of white infants among cases with PA. 38 Sadiq and colleagues reported an excess of complex congenital heart defects in Asian infants in Birmingham, and an excess of COA among non-Asian infants. 39 It has been suggested that consanguinity could have an impact on the prevalence of birth defects in some regions of the UK, but the evidence remains unclear. Furthermore, the national impact of consanguinity was felt to be adequately represented by the Northern Region population data.…”
Section: Birth Prevalencementioning
confidence: 99%
“…9 Early treatment of CHD may prevent a serious risk of avoidable mortality, morbidity, and handicaps. 10 The aim of this study was to verify the pattern and frequency of CHD in pediatric patients at the Cardiac Research Institute of Kabul Medical University. In Afghanistan most births still take place at home, so it is nearly impossible to screen all the new borns for congenital anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…We found that among our CHD subjects, 20% had cyanotic heart disease and 80% had acyanotic heart disease, similar to results reported in both local and international studies. [2][3][4][5][6][7][8][9][10][11][12] The ASD and VSD were the most common lesions in our study subjects. Of our CHD subjects, we noted that 103/235 (43.8%) had ASD, which was similar to results from previous studies in neighboring Pakistan, 32.1% at the Punjab Institute of Cardiology (PIC), Lahore, 39.9% at the National Institute of Cardiology Karachi, and 38.16% at the Siddique Sadiq Memorial Trust Hospital, Gujranwala.…”
Section: Discussionmentioning
confidence: 99%